Singlism in an Asian Culture: An Exploratory Study - LAU, Ivy Yee-Man (Institutional Knowledge at Singapore Management University, 2010)
Exploratory studies were conducted to see if singlism (negative stereotypes of and discrimination against singles, DePaulo & Morris, 2006) can be generalized to Asian cultures. Results were generally comparable to findings from North America with nuanced findings showing a difference in people’s judgment when different evaluation criteria are used.